Flourishing in critical dialogue - Tyler J. VanderWeele; Brendan W. Case; Ying Chen; Richard G. Cowden; Byron Johnson; Matthew T. Lee; Tim Lomas; Katelyn G. Long (Elsevier, 2023)
We discuss various critiques of the research literature on flourishing. We fully agree with calls for greater attention to qualitative work, to cultural differences, and to questions of power and justice concerning flourishing. We argue, however, that in spite of notable differences in understandings of flourishing across cultures, there is also a great deal that is held in common, including on topics considered by some as more controversial, such as character and virtue. We also argue that while qualitative research and understanding is important, it is likewise important not to be dismissive of rigorous quantitative research even if certain groups find its results to be unappealing. We further propose that the best way to navigate diverse understandings of flourishing in pluralistic contexts is to identify those aspects of flourishing which are in fact held in common, and to promote these together, but then to acknowledge that certain understandings of flourishing will vary by culture or religious tradition, and to allow and enable each community to exposit, study, and promote flourishing, as it understands it, in critical dialogue with others.